AAPS Workshop Report on ICH M10 - Brian Booth; Faye Vazvaei; Eric Fluhler; Heather Myler; Eric Woolf (The AAPS Journal, 2020)
Over the last decade, several regulatory guidelines on bioanalytical method validation (BMV) have been issued by regulatory agencies around the world. This has left the bioanalytical community struggling with regional differences in regulatory expectations when preparing for global pharmaceutical submissions. The International Council for Harmonization of Technical Requirements for Pharmaceuticals for Human Use (ICH) has the mission to achieve greater harmonization worldwide to ensure that safe, effective, and high-quality medicines are developed and registered in the most resource-efficient manner. Following calls for harmonization, ICH-selected bioanalytical method validation and sample analysis among its topics for guidance development and earlier this year released a draft guideline (M10) on BMV for public consultation. In response, the American Association of Pharmaceutical Scientists (AAPS) held a 3-day workshop to provide a forum for regulatory, industry, and academic scientists to discuss the guideline and hear various points of view on key aspects. While there was agreement that the draft guideline is generally well written and comprehensive, specific topics generated considerable discussion and, in some cases, revision recommendations for consideration by the expert working group (EWG) responsible for the guideline content. This report provides a summary of the workshop proceedings.

Workshop Report: Crystal City V—Quantitative Bioanalytical Method Validation and Implementation: The 2013 Revised FDA Guidance - Brian Booth; Mark E. Arnold; Binodh DeSilva; Lakshmi Amaravadi; Sherri Dudal; Eric Fluhler; Boris Gorovits; Sam H. Haidar; John Kadavil; Steve Lowes; Robert Nicholson; Marie Rock; et al. (The AAPS Journal, 2015)

Repeat Analysis and Incurred Sample Reanalysis: Recommendation for Best Practices and Harmonization from the Global Bioanalysis Consortium Harmonization Team - Eric Fluhler; Faye Vazvaei; Puran Singhal; Petra Vinck; Wenkui Li; Jignesh Bhatt; Theo de Boer; Ajai Chaudhary; Masahiro Tangiuchi; Vinicius Rezende; Dafang Zhong (The AAPS Journal, 2014)